Pengendalian Penyakit Busuk Buah Phytophthora pada Kakao dengan Cendawan Endofit Trichoderma asperellum - Andi Akbar Hakkar; Ade Rosmana; Muhammad Danial Rahim (Jurnal Fitopatologi Indonesia, 2014)
The Phytophthora pod rot (PPR) caused by Phytophthora palmivora is one of important diseases affecting the decrease of cacao productivity. The use of endophytic Trichoderma have a big potential for controlling this disease. The rate of PPR incidence in twelve weeks after three times application by spraying of ART-4/G.J.S 09-1559 isolate of Trichoderma asperellum with concentration of 1 g L-1, 2 g L-1, 4 g L-1 was 5.4%, 5.3%, and 3.7%, respectively per week; while the rate of PPR incidence on control was 8.4% per week. Apparently healthy pods pretreated with above concentrations of T. asperellum in field showed 30, 0, and 0% infested by PPR on its surface, respectively after one week incubation in laboratory, compared to a 90% of surface infestation by PPR on control. After 12 week of inoculation, T. asperellum was recovered from pod tissue. This data demonstrated the potential of T. asperellum as bio control agent of PPR disease on cacao.